2012
DOI: 10.1073/pnas.1018858109
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor prevents p53-dependent apoptosis in breast cancer

Abstract: More than two-thirds of breast cancers express the estrogen receptor (ER) and depend on estrogen for growth and survival. Therapies targeting ER function, including aromatase inhibitors that block the production of estrogens and ER antagonists that alter ER transcriptional activity, play a central role in the treatment of ER+ breast cancers of all stages. In contrast to ER− breast cancers, which frequently harbor mutations in the p53 tumor suppressor, ER+ breast cancers are predominantly wild type for p53. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 57 publications
8
137
0
Order By: Relevance
“…Similarly, in human breast cancer cells, estrogen downregulates the P53 target genes, including ATF3, BGT2 and TRAF4, which are involved in P53-mediated apoptosis (Bailey et al, 2012). We found that at 33-34 dpf, btg2 mRNA was downregulated while traf4a mRNA had similar levels of expression in zar1 mutant ovaries and control sibling ovaries (Fig.…”
Section: Estrogen Treatment Restores Oogenesis In Zar1 Mutantssupporting
confidence: 58%
“…Similarly, in human breast cancer cells, estrogen downregulates the P53 target genes, including ATF3, BGT2 and TRAF4, which are involved in P53-mediated apoptosis (Bailey et al, 2012). We found that at 33-34 dpf, btg2 mRNA was downregulated while traf4a mRNA had similar levels of expression in zar1 mutant ovaries and control sibling ovaries (Fig.…”
Section: Estrogen Treatment Restores Oogenesis In Zar1 Mutantssupporting
confidence: 58%
“…In tumors with wild-type p53, p53 responses can be inhibited by downregulating p53 activity or its effectors' activity. For instance, in estrogen receptor-positive (ER þ ) breast cancers, ER prevents the p53-mediated apoptotic response by directly interacting with p53 (6).…”
Section: Traditional Tumor Suppressor Functions Of P53mentioning
confidence: 99%
“…56,57 The regulation of cell death by the p53 protein is quite complex, acting both at the level of autophagy, 58 lysosomes, 59 or at the core machinery of programmed cell death. [60][61][62][63][64][65] In addition to DNA damage response and cell death, p53 plays a crucial role in regulating cellular senescence [66][67][68] by interacting, for example, with MageA2, 69 PATZ1, 70 4E-BP1, 71 mTOR, 72,73 highlighting the vast complexity of this crucial regulation.…”
Section: Introductionmentioning
confidence: 99%